Facility layout decision model for small and medium shopping mall - Haque, A. K. M. Ahasanul; Irfath Jahan, Syeada; Chowdhury, Naila Anwar; Sarker, Md Atiqur Rahman (Research Publishing Academy, 2021)
This study is based on a case analysis where a particular medium size shopping mall has been taken for observation. Field work has been utilized as the ground for suggesting a new model for a shopping mall layout. Various factors necessitated the undertaking of this particular study. First and foremost, many methods prevail in business research, but they are hardly understood by practitioners due to the inclusion of advanced mathematical techniques. Secondly, for the purpose of suggesting a new shopping mall layout, this study has taken into account a number of vital factors which were not previously considered in any earlier methods. The significance of retail trading in small and medium size shopping malls has been confirmed through many reports available in contemporary literature. Therefore, today’s highly competitive retail industry demands a well-designed facility layout to protect the interest of both traders as well as customers. In light of this view, the current research analyzed a real facility layout of a me